2018
DOI: 10.3892/ol.2018.8201
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of NF-κB regulated genes in sporadic colorectal cancer patients

Abstract: Colorectal cancer (CRC) is the fourth leading worldwide cause of cancer-associated mortalities. Nuclear factor-κB (NF-κB) is a transcriptional regulator of multiple genes associated with CRC. Tumor tissue were compared with normal adjacent mucosa from 30 sporadic patients with CRC were investigated. A total of 8 non-CRC patients were analyzed as a control group. In the present study, the protein expression of NF-κB/p65 was detected by immunohistochemistry, and the gene expression profiles of cyclin D1 , prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…To further explore the molecular mechanism of the AuNP-coated SEMS-mediated PTA, mRNA levels of various tumor markers, carcinoembryonic antigen (Cea), mitogen-activated protein kinase 1 (Mapk1), c-Jun N-terminal kinase (Jnk), cyclin-dependent kinase 6 (Cdk6), transforming growth factor-beta (Tgf-β), cyclooxygenase 2 (Cox-2), p65, tumor necrosis factor-alpha (Tnf-α), and cluster of differentiation 133 (Cd133), were examined by quantitative reverse-transcription polymerase chain reaction (qRT-PCR) (Table S1, Supporting Information). Among these, we found a significantly lower Mapk1 expression in group C ( p = 0.02) (Figure c), which was consistent with the reduced infiltration and smaller tumor size.…”
Section: Resultsmentioning
confidence: 99%
“…To further explore the molecular mechanism of the AuNP-coated SEMS-mediated PTA, mRNA levels of various tumor markers, carcinoembryonic antigen (Cea), mitogen-activated protein kinase 1 (Mapk1), c-Jun N-terminal kinase (Jnk), cyclin-dependent kinase 6 (Cdk6), transforming growth factor-beta (Tgf-β), cyclooxygenase 2 (Cox-2), p65, tumor necrosis factor-alpha (Tnf-α), and cluster of differentiation 133 (Cd133), were examined by quantitative reverse-transcription polymerase chain reaction (qRT-PCR) (Table S1, Supporting Information). Among these, we found a significantly lower Mapk1 expression in group C ( p = 0.02) (Figure c), which was consistent with the reduced infiltration and smaller tumor size.…”
Section: Resultsmentioning
confidence: 99%
“…In cancer cells however, NF-κB pathway is often dysregulated so that cells could evade apoptosis and proliferate uncontrollably. In the context of colorectal cancer, NF-κB and some of its regulated genes, have been found to be expressed at higher levels in tumors samples, and appear to correlate with a worse prognosis ( 50 , 51 ). It has been shown that NF-kB induces transcription of many genes, including pro-inflammatory cytokines, such as IL-8, IL-6 and TNF-α ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…The final staining score was obtained by adding the staining intensity to the extent of staining. Scores equal to or greater than 3 were considered positive [ 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%